Impacts of precipitation and temperature on crop yields in the Pampas - Veron, Santiago Ramón (2015)
Understanding regional impacts of recent climate trends can help anticipate how further climate change will affect agricultural productivity. We here used panel models to estimate the contribution of growing season precipitation (P), average temperature (T) and diurnal temperature range (DTR) on wheat, maize and soy yield and yield trends between 1971 and 2012 from 33 counties of the Argentine Pampas. A parallel analysis was conducted on a per county basis by adjusting a linear model to the first difference (i.e., subtracting from each value the previous year value) in yield and first difference in weather variables to estimate crop sensitivity to interannual changes in P, T, and DTR. Our results show a relatively small but significant negative impact of climate trends on yield which is consistent with the estimated crop and county specific sensitivity of yield to interannual changes in P, T and DTR and their temporal trends. Median yield loss from climate trends for the 1971−2012 period amounted to 5.4 % of average yields for maize, 5.1 % for wheat, and 2.6 % for soy. Crop yield gains for this time period could have been 15–20 % higher if climate remained without directional changes in the Pampas. On average, crop yield responded more to trends in T and DTR than in P. Translated into economic terms the observed reductions in maize, wheat, and soy yields due to climate trends in the Pampas would equal $1.1 B using 2013 producer prices. These results add to the increasing evidence that climate trends are slowing yield increase.